(untitled) - VERMA, N.K.; PITLIYA, R.L; VAIDYA SURESH C. AMETA*., V.K. (Asian Journal of Chemistry, 2010)
Methylene blue-sensitized oxidation of 0,0-dimethyl,0-4-nitro-m-tolyl phosphorothioate (fenitrothion) by singlet oxygen has been carried out in methanol. Photo-product has been isolated and characterized as fenitrooxon. A tentative mechanism for the reaction has been proposed involving participation of singlet oxygen.